Effect of iron application methods on grain yield and iron concentration of rice under different nitrogen levels - Ghani Usman; Khan Ameer; Shahzad Ali; Fizza Ayesha; Shahzad Muhammad; Gul Hameed; Mohamed Soufiane; Gul Shareef (Acta Agriculturae Serbica, 2023)
Rice is a staple cereal crop that helps food security and overcomes nutrition problems. The application of synthetic nitrogen (N) fertilizers results in the improvement of nutrient concentration. Therefore, iron (Fe) biofortification in rice can be improved by altering Fe application methods under different N levels. We made a comprehensive assessment on this, analyzing Fe concentration in the root, shoot and grain of the Super Basmati cultivar raised under two N levels (80 kg h-1 and 160 kg h-1) with Fe applied through the soil and/or foliar supply at different growth stages. The results showed that agronomic traits such as plant height, chlorophyll contents, number of productive tillers, panicle length, number of spikelets per panicle, 100-grain weight, grain yield, biological yield, and harvest index were significantly influenced by Fe application methods and N levels. Soil + Foliar application of Fe at 80 kg ha-1 of N level had maximum biological yield (18.70 g/pot), grain yield (7.31 g/pot), and harvest index (60.87%). Results revealed that iron concentration was significantly influenced by Fe application methods under different N levels, and their interaction showed significant influence. The highest values of Fe concentration in the shoot (300.50 ppm), root (446.63 ppm), and grain (141.13 ppm) were observed under 80 kg ha-1 N application. Results suggest that Fe biofortification has the potential to improve the Fe content in rice grain by various application methods with optimal N availability.